Faktor-Faktor Yang Mempengaruhi Keputusan Revaluasi Aset Tetap Pada Perusahaan Pertambangan - Frederica, Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The objective of this research is to obtain empirical evidence about the effect of leverage, fixed asset intensity, firm size, and operating cashflow on fixed asset revaluation in mining companies listed on the Indonesia Stock Exchange (IDX) during the year 2015-2019. This study uses secondary data. This research is conducted with a sample of 125 mining companies data with the technique used in this study is purposive sampling. The research data was processed using Statistical Product and Service Solution software for Windows version 23 (SPSS version 23) and Microsoft Excel 2013. The results of this research show that firm size has a significant influence on fixed asset revaluation, while leverage, fixed asset intensity, and operating cashflow do not have a significant effect on fixed asset revaluation.